Characterization of patients with clinical diagnosis of Histoplasmosis in the "Hospital Universitario San Ignacio" between 2012-2016 - Isabel Cristina Cuéllar (Asociación Colombiana de Infectología, 2019)
Introduction: Disseminated histoplasmosis is a common presentation in immunosuppressed patients. The introduction of new diagnostic methods and the improvement of the survival of patients with HIV could have changed the clinical characteristics of patients with this disease. The objective of this study is to describe the demographic characteristics, clinical and methods for diagnosis of this disease in a high conplexity institution in Colombia during the last five years. Methods: A serie of cases was conducted, including patients diagnosed with histoplasmosis managed at the San Ignacio University Hospital in Bogotá (Colombia) between January 2012 and December 2016. The cases were selected using an automatic tool for searching in health electronic records (DISEARCH). Results: 34 patients were included, 73.5% with HIV. The disease was more symptomatic in patients with HIV. The most frequent symptoms were fever and cough (80%), followed by diarrhea (47%) and skin manifestations (35%). The histopathological study was the most frequent confirmation method. The urinary antigen was positive in 92.8% of the patients, in whom the test was performed. Autoimmune diseases were the main cause associated in HIV negative patients. Conclusions: The clinical characteristics of patients with histoplasmosis are similar to those described in previous studies in Colombia. It was remarkably the high prevalence of diarrhea and cutaneous manifestations. The urinary antigen for histoplasma and skin biopsies are excellent diagnostic methods, less invasive and with rapidly available results